Niveles explicativos y ontología de la mente en la psicología evolucionista - Fernández Acevedo, Gustavo (Revista de Filosofía, 2007)
In this article I defend two theses related to the ontology of the mind and the conception of explanatory levels supposed by evolutionary psychology. First, that the theory of mind adopted by this program can not remove all dualist remnant and present an acceptable picture of mind-body relationship. Second, that the difficulties presented by the ontological hypothesis, in addition to certain plausible theses on the explanatory compatibility, reduce in wide measure the attractiveness of pluralism of levels defended.